Building ESP Corpus-driven Specialized Words in Vocational Education in Saudi Arabia (British Journal of Multidisciplinary and Advanced Studies, 2024)
Both corpus revolution and advances in computer-based technologies have a remarkable impact on teaching and learning English as well as corpus studies. Nevertheless, Jablonkai (2020) observed that professional or occupational programs are less studied or researched compared to academic focus courses. Therefore, this paper is based on a replication study of Coxhead and Demecheleer (2018, cited in Jablonkai and Csomay, 2023) to develop ESP corpus-driven specialized words in vocational education. This process is tackled in three main phases: collection, computerization, and annotation of data. Data collection will be in mixed method from written and spoken ESP corpuses before using qualitative and quantitative analysis to measure frequency, key words and concordance comparing with other ESP corpora. The computerization phase will be based on lexical frame analysis (LFA) framework to convert a text to corpus, and this is quite labor-intensive part of creating the corpus. Finally, the annotation phase includes further lexical information covering semantic, pragmatic, and syntactic details. The first phase, data collection and analysis, will be reflected in Coxhead and Demecheleer's (2018) and the remaining two phases, annotating and computerizing data, will be elaborated through using LFA with two similar Business English corpora, PROLEX and PROCOMPARE, cited in Vincent (2009). The findings and conclusion of using three corpora could be effective in conducting this study as a preparation for creating a comprehensive technical corpus covering specialized words for all oil industry majors in my context. Further research could be conducted in the service of replication studies and expanding areas of ESP and vocabulary research using corpora.